The changing pattern of foreign trade - F. Akin Olaloku (Intereconomics, 1975)
Like many of the other less developed countries, one of the major sources of growth in the Nigerian economy is foreign-oriented. With exports accounting for close to one-fifth of the Gross Domestic Product and imports representing about the same proportion, external trade since World War II has been of particular importance to the economy.
Keywords: 330; Nigeria